Anemia and intestinal parasites in farmers and family members and sheep in two agro-ecological zones in Senegal - Walden, Heather D.S. (One Health, 2021)
The burden of anemia in Senegal is high, particularly in children and women in rural households. The main objectives of the study reported here were (i) to measure and compare the prevalence of anemia and intestinal parasitic infections in farmers and family members and sheep in two agro-ecological zones in Senegal and (ii) to examine the association between anemia and age or sex in farmers and family members. The study was conducted in Mpal (250 km from Dakar, the capital city) and Diawara (700 km from Dakar, a remote location near the Malian border). In humans, the prevalence of anemia was higher in Diawara (64/86 = 74%), compared to Mpal (13/29 = 45%) (p < 0.01). Using logistic regression, the odds of anemia were 20.3, 5.7, and 3.2 times higher in children 1–4 years old, children 5–12 years-old, and teenagers 13–19 years old, respectively, compared to adults 20–60 years old, after controlling for study site and sex (p < 0.05). In Diawara, the odds of anemia were 2.9 times higher in women, compared to men, after controlling for age (p = 0.06). The prevalence of intestinal parasites (Giardia sp.) was the same (7%) at both locations. In sheep, the prevalence of low packed cell volume (PCV) and low body condition was higher in Diawara (48/60 = 60% and 11/60 = 18%, respectively), compared to Mpal (23/46 = 50% and 0/46 = 0%, respectively) (p < 0.05). Clinical anemia was associated (p < 0.01) with low PCV and a positive diagnosis of H. contortus. Overall, the prevalence of anemia was higher in farmers and family members and owned sheep in Diawara. In addition, anemia was more common in children and women, an indication that intra-household food allocation may be regulated in favor of men and older age groups. The consequences of livestock affected with anemia and undernutrition can be significant. High morbidity and mortality in livestock can lead to low household income, inadequate household access to and individual consumption of animal source foods, and subsequent risk of anemia in children and women in rural households in Senegal.